The place of lament art between genres and poetic purposes in Kurdish folklore poetry (Northern Kurmanji) as a model - Hussain, Haliz; Khalil, Kamran (Humanities Journal of University of Zakho, 2022)
Death is the fate of every living person, so it is considered the main structure of the existence of the art of lamentation. We conclude from this that death has existed since the beginning of human life, and the art of lamentation has emerged from it, and as long as there is life and death, lamentation will continue to exist. Therefore, lamentation is considered an effective way for a person to relieve his pain. As a result of his various sorrows, it is also considered one of the most important topics in Kurdish folklore poetry. The present study, is built on the basis of the hypothesis, which says that lamentation is a poetic purpose that dominates Kurdish folklore poetry, and we cannot change this hypothesis to any other type or purpose in folkloric poetry. Moreover,In this study, we tried to find out whether lament art has a definitive and specific place in Kurdish folklore poetry (Northern Kurmanji) or not? And to what extent has the poetry of folkloric lament adhered to poetic rhyme? In our study (the place of lamentation between genres and poetic purposes in Kurdish folklore poetry, (Northern Kurmanji) as an example), we try to show the place of lamentation between genres and poetic purposes in Kurdish folklore poetry (Northern Kurmanji). At the beginning of our research , the subject of the relationship of death with literature and the beginnings of lamentation within Kurdish folklore poetry has been discussed , then we touched upon the subject of the place of lamentation art among genres and poetic purposes in Kurdish folklore poetry. We applied the descriptive analytical method in this study.